Getting your game out there : practical advice for getting a video game noticed in an insanely crowded marketplace - Imms, Jason (O'Reilly, 2017)
"Video game journalist Jason Imms has seen some of the best and worst games, game pitches, and game press releases the world has ever known. This experience, and the associated experience of seeing which games sell and which games don't, compelled him to create this instructional series on how to best promote a game in today's overheated video game market. This course offers current and aspiring game developers an insider's look at games marketing, networking, crowdfunding, social media presence, promotion, and how to be noticed by the press and influencers."--Resource description page.